Exterior wall flame-retardant material prepared from waste plastics and method

By combining the mixed plastic of waste polystyrene and polycarbonate with a variety of functional additives and using a multi-step process to prepare high-performance exterior wall flame retardant materials, the problems of poor material performance and waste plastic treatment problems in the prior art are solved, and the material performance is significantly improved and the efficient utilization of waste plastics is achieved.

CN119842165APending Publication Date: 2025-04-18DONGGUAN ZHONGYI NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202510112248.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

It is difficult to develop high-performance exterior wall flame retardant materials in the prior art, and how to efficiently utilize waste plastics is also an environmental problem.

Method used

By using mixed plastics of waste polystyrene and polycarbonate as base material, and adding waste liquid crystal display material fragments, bio-based degradable polyester polyols, nano-silicon carbide and boron nitride composite powder, phosphorus-nitrogen-silicon-boro quaternary synergistic flame retardant, composite reinforcement of waste basalt fiber and graphene, composite materials of photocatalytic nano-titanium dioxide and activated carbon, and intelligent shape memory polymer microcapsules and other components, high-performance exterior wall flame retardant materials are prepared through high-speed mixing, twin-screw extrusion, microwave-assisted chemical crosslinking, magnetic field-assisted orientation molding and low-temperature plasma surface treatment and other processes, high-performance extinguishing of the outer wall flame retardant materials are prepared.

Benefits of technology

The material has significantly improved its mechanical properties, flame retardant properties, thermal conductivity, biodegradability and self-cleaning functions, which can effectively meet the strict requirements of modern buildings for exterior wall materials, and at the same time achieve efficient utilization of waste plastics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005256933340000201
    Figure BDA0005256933340000201
  • Figure BDA0005256933340000211
    Figure BDA0005256933340000211
  • Figure BDA0005256933340000221
    Figure BDA0005256933340000221
Patent Text Reader

Abstract

The invention belongs to the field of environment-friendly materials, and particularly discloses a method for preparing a high-performance exterior wall flame-retardant material from waste plastics. Through a unique formula, for example, waste polyethersulfone and the like are used as base materials, a waste basalt fiber and MOF derived carbon nanosheet composite reinforced phase, multiple novel flame retardants and the like are added, and innovative processes including pulsed electric field treatment, carbon dioxide supercritical fluid assistance and the like are combined, so that the material performance is remarkably improved. The tensile strength, the thermal stability, the flame retardant property and the like of the material are greatly enhanced, the material also has multiple functions of flexibility, self-cleaning, antibiosis and the like, and a new way is provided for high-value utilization of waste plastics and performance optimization of exterior wall materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmentally friendly materials, and in particular to an exterior wall flame retardant material prepared from waste plastics. Background Art

[0002] With the development of the construction industry, the performance requirements for exterior wall materials are increasing day by day, and the disposal of waste plastics has also become an environmental problem. Traditional exterior wall materials have limitations in terms of flame retardancy and mechanical properties, and it is difficult to meet the needs of modern construction. The accumulation of a large amount of waste plastics not only occupies land resources, but also causes serious pollution to the environment.

[0003] At present, although there are some studies on the use of waste plastics to prepare materials, most of them have problems such as poor performance, complicated processes or high costs. For example, the flame retardant properties of conventional waste plastic recycling products can only reach ordinary levels and cannot meet the stringent fire protection requirements of building exterior walls; in terms of mechanical properties, it is often difficult to balance strength and toughness. In addition, some processes cannot effectively disperse additives when processing waste plastics, resulting in uneven material properties. Therefore, it is urgent to develop a method that can both efficiently utilize waste plastics and prepare high-performance exterior wall flame retardant materials. Summary of the invention

[0004] The invention provides an exterior wall flame retardant material prepared from waste plastics. The material takes a mixed plastic of waste polystyrene (PS) and polycarbonate (PC) as a base material, wherein in 80-100 parts by weight of the mixed plastic, the weight ratio of PS to PC is 3:2; the material comprises 5-10 parts by weight of waste liquid crystal display material fragments, 8-10 parts by weight of bio-based degradable polyester polyol, 3-5 parts by weight of nano silicon carbide and boron nitride composite powder, 4-6 parts by weight of a phosphorus-nitrogen-silicon-boron quaternary synergistic flame retardant, 6-8 parts by weight of a composite reinforcement of waste basalt fiber and graphene, 2-5 parts by weight of a composite material of photocatalytic nano titanium dioxide and activated carbon, 5-8 parts by weight of a hyperbranched polymer and 0.5-1 parts by weight of an intelligent shape memory polymer microcapsule.

[0005] Furthermore, the particle size of the waste liquid crystal display material fragments is micrometer level, and they are obtained by crushing the waste liquid crystal display materials.

[0006] Furthermore, the bio-based degradable polyester polyol is synthesized using biomass as raw material and is used to improve the flexibility and biodegradability of the material.

[0007] Furthermore, in the nano-silicon carbide and boron nitride composite powder, the weight ratio of nano-silicon carbide and boron nitride is 2:1, which is used to enhance the mechanical properties and thermal insulation properties of the material. After a large number of experimental studies, it was found that when nano-silicon carbide and boron nitride are compounded at a weight ratio of 2:1, a relatively ideal reinforced structure can be formed in the waste plastic system. Nano-silicon carbide, with its high hardness and high strength, plays a skeletal support role inside the material, effectively improving the mechanical properties of the material; boron nitride uses its good thermal insulation properties and synergistic effect with nano-silicon carbide to further enhance the thermal insulation properties of the material, so that the material achieves a better balance in mechanics and thermal insulation.

[0008] Furthermore, the phosphorus-nitrogen-silicon-boron quaternary synergistic flame retardant exerts a flame retardant effect in both the gas phase and the condensed phase to improve the flame retardant efficiency.

[0009] On the other hand, a process for preparing exterior wall flame retardant materials from waste plastics includes washing, drying and crushing the waste plastics;

[0010] Add all components except smart shape memory polymer microcapsules into a high-speed mixer and premix at 80-100°C for 15 minutes;

[0011] The mixed material is transferred to a twin-screw extruder and melt-blended at 180-220°C with a screw speed of 150-180 rpm;

[0012] During the blending process, the smart shape memory polymer microcapsules were added through a side feeding device and the blending was continued for 5 minutes;

[0013] The blended materials were treated at a microwave power of 600-800 W for 3-5 minutes using a microwave-assisted chemical cross-linking process;

[0014] Using the carbon dioxide supercritical fluid plasticizing process, supercritical carbon dioxide is injected into the material at a pressure of 10-12MPa and a temperature of 35-40°C;

[0015] The magnetic field assisted orientation molding process is used, and a magnetic field of 0.5-1T is applied during the injection molding process;

[0016] The formed material is subjected to low-temperature plasma surface treatment and grafting modification process, treated in a plasma environment with a power of 100-150W for 3-5 minutes, and then subjected to grafting modification reaction.

[0017] Furthermore, the microwave-assisted chemical cross-linking process is used to promote the cross-linking between waste plastics and additives, thereby improving the stability of the material.

[0018] Furthermore, the magnetic field-assisted orientation molding process enables magnetic additives or components to be oriented during the molding process, thereby improving the anisotropic properties of the material.

[0019] Furthermore, the carbon dioxide supercritical fluid plasticization process improves the processing performance of waste plastics and reduces processing temperature and energy consumption.

[0020] Furthermore, the exterior wall flame retardant material prepared by the preparation process has a tensile strength of 70 MPa, which is 35% higher than that of the material without the corresponding formula components added and the corresponding process; the limiting oxygen index is increased from 24% to 35%, reaching V-0 level in the UL-94 vertical combustion test; the thermal conductivity is reduced by 40%, reaching 0.05 W / (m·K); it has good self-cleaning and air purification functions; the biodegradability is improved, and the mass loss rate reaches 20% after being buried in the soil for 6 months; the impact resistance is increased by 50%, and the impact strength reaches 45 kJ / m 2 ; It has self-repairing function; the surface performance is significantly improved, the surface hardness is increased by 20%, and the wear resistance is enhanced; during the processing, the processing temperature is reduced by 20-30℃ and the energy consumption is reduced by 15%-20%.

[0021] Beneficial effects:

[0022] Nano silicon carbide provides skeleton support, and boron nitride synergistically enhances; the composite reinforcement of waste basalt fiber and graphene provides high-strength support; hyperbranched polymer enhances intermolecular interaction and cross-linking, and jointly improves tensile strength. The composite reinforcement of waste basalt fiber and graphene absorbs impact energy and prevents crack propagation, and the hyperbranched polymer enhances toughness, disperses stress, and improves impact resistance. The phosphorus-nitrogen-silicon-boron quaternary synergistic flame retardant acts simultaneously in the gas phase and the condensed phase, blocking the combustion chain reaction and forming a heat-insulating and oxygen-isolating layer, improving the limiting oxygen index, and making UL-94 reach V-0 level. The thermal insulation of boron nitride in the composite powder of nano silicon carbide and boron nitride cooperates with nano silicon carbide, and the internal structure of the composite material of photocatalytic nano titanium dioxide and activated carbon jointly reduces the thermal conductivity. Photocatalytic nano titanium dioxide photocatalytically decomposes organic matter, and activated carbon adsorbs pollutants, giving the material self-cleaning and air purification functions. Bio-based degradable polyester polyols are degradable components, making the material easily decomposed by microorganisms and improving biodegradability. Smart shape memory polymer microcapsules rupture under external stimulation to release repair agents, achieving self-repair of the material. Low-temperature plasma surface treatment and grafting modification processes change the chemical structure and roughness of the material surface. Some ingredients in the formula enhance the overall strength of the material, and jointly improve the surface hardness and wear resistance. Carbon dioxide supercritical fluid plasticization process reduces the material melt viscosity, and microwave-assisted chemical cross-linking process promotes cross-linking, jointly reducing processing temperature and energy consumption.

[0023] In terms of mechanical properties, the tensile strength of materials based on waste polyethersulfone has increased from 50MPa to 75MPa, and the bending strength has also been significantly improved. For example, the bending strength of materials based on a mixture of waste polylactic acid and polyhydroxyalkanoate has increased from 45MPa to 65MPa, which can effectively withstand the external forces of building structures. In terms of thermal stability, the mass retention rate at 400°C has been greatly improved, such as the material containing MOF-derived carbon nanosheets has increased from 40% to 60%, which effectively ensures the structural stability of the material under high temperature conditions. The flame retardant performance has achieved a qualitative leap. In the UL-94 vertical combustion test, a variety of materials have directly reached the V-0 level from no flame retardant grade or low grade, greatly reducing the fire hazard. In addition, the material has many additional functions. Improved flexibility makes the material less prone to brittle cracking, and improved water resistance reduces the performance degradation caused by moisture; photocatalytic performance can degrade harmful gases, and antibacterial performance can effectively inhibit bacterial growth, providing health protection for the indoor environment; photochromic performance can adjust indoor light according to light intensity to improve living comfort. Specific implementation method:

[0024] Example 1

[0025] Recipe Implementation:

[0026] Waste polystyrene (PS) is used as the base material, accounting for 70% by mass.

[0027] Adding 10% of discarded liquid crystal display material fragments can enhance the heat insulation and flame retardant properties.

[0028] Add 10% bio-based degradable polyester polyol to improve flexibility and biodegradability.

[0029] Mix 5% of nano silicon carbide and boron nitride composite powder to improve mechanical and thermal insulation properties.

[0030] Add 5% of phosphorus-nitrogen-silicon-boron quaternary synergistic flame retardant to enhance the flame retardant effect.

[0031] Process implementation:

[0032] After the waste plastic is crushed, it is premixed with other formulation components in a high-speed mixer for 15 minutes.

[0033] The mixture was transferred to a twin-screw extruder and melt-blended at 180-200°C with a screw speed of 160 rpm.

[0034] A microwave-assisted chemical cross-linking process was used with a microwave power of 700 W and a treatment time of 4 minutes.

[0035] The exterior wall material samples were made by injection molding.

[0036] Enhancement Description:

[0037] Compared with ordinary PS materials without the above-mentioned formula components and microwave-assisted chemical cross-linking process, the tensile strength increased from 40MPa to 55MPa, an increase of 37.5%. The nano-silicon carbide and boron nitride composite powder effectively enhanced the internal structure of the material, and the microwave-assisted chemical cross-linking made the molecular cross-linking tighter, improving the overall strength.

[0038] The thermal conductivity coefficient dropped from 0.12W / (m·K) to 0.07W / (m·K), a decrease of 41.7%. The waste liquid crystal display material fragments and nano-silicon carbide and boron nitride composite powders jointly constructed a high-efficiency thermal insulation structure, significantly improving the thermal insulation performance.

[0039] In the UL-94 vertical burning test, the flame retardant level was improved from no flame retardancy to V-1 level. The phosphorus-nitrogen-silicon-boron quaternary synergistic flame retardant and the waste liquid crystal display material fragments work together at high temperatures to form a good flame retardant barrier.

[0040] In the biodegradability test, after being buried in the soil for 6 months, the mass loss rate increased from almost 0 to 15%. The introduction of bio-based degradable polyester polyols effectively improved the biodegradability of the material.

[0041] Example 2

[0042] Recipe Implementation:

[0043] The base material is a mixture of waste polycarbonate (PC) and polyethylene (PE) in a mass ratio of 4:6.

[0044] Adding 8% of waste basalt fiber and graphene composite reinforcement improves tensile strength and conductivity.

[0045] Adding 10% of the composite material of photocatalytic nano titanium dioxide and activated carbon gives it self-cleaning and air purification functions.

[0046] 6% of hyperbranched polymer is mixed in as a toughening agent to improve impact resistance.

[0047] 4% of smart shape memory polymer microcapsules are introduced to achieve self-healing function.

[0048] Process implementation:

[0049] First, the waste plastics are mixed and crushed, and premixed with other formulation components in a high-speed mixer for 10 minutes.

[0050] Enter into the twin-screw extruder, melt blend at 170-190°C, and the screw speed is 150rpm.

[0051] A 0.8T magnetic field was applied during the molding process, and a magnetic field-assisted orientation molding process was adopted.

[0052] Finally, the exterior wall material sample is obtained by injection molding.

[0053] Enhancement Description:

[0054] Impact strength from 25kJ / m 2 Increased to 40 kJ / m 2 The hyperbranched polymer and magnetic field-assisted orientation molding process work together to enhance the toughness and internal structural order of the material, enabling it to better absorb impact energy.

[0055] The organic pollutants on the surface of the material decomposed by 80% within 3 days under light, showing good self-cleaning function. The composite material of photocatalytic nano-titanium dioxide and activated carbon effectively decomposed pollutants under light.

[0056] The purification rate of harmful gases such as formaldehyde reaches 70% within 24 hours. Activated carbon absorbs harmful gases, and photocatalytic nano-titanium dioxide decomposes them to achieve efficient air purification.

[0057] When a tiny scratch appears on the surface of the material, after being treated at 60°C and 0.5MPa for 10 minutes, the mechanical properties of the scratched area recover to 85% of the original state. The smart shape memory polymer microcapsules release the repair agent under specific conditions, effectively repairing the material damage.

[0058] In the direction of the magnetic field, the tensile strength increased by 20% to 65MPa. The magnetic field-assisted orientation molding process makes the composite reinforcement of waste basalt fiber and graphene oriented in the direction of the magnetic field, enhancing the mechanical properties in this direction.

[0059] Example 3

[0060] Recipe Implementation:

[0061] The base material is waste polyvinyl chloride (PVC), which accounts for 75% of the mass.

[0062] Adding 12% of discarded liquid crystal display material fragments can enhance the heat insulation and flame retardant properties.

[0063] Add 8% bio-based degradable polyester polyol to improve flexibility and biodegradability.

[0064] Mix 3% of nano silicon carbide and boron nitride composite powder to improve mechanical and thermal insulation properties.

[0065] 2% of phosphorus-nitrogen-silicon-boron quaternary synergistic flame retardant is introduced to enhance the flame retardant effect.

[0066] Process implementation:

[0067] The waste plastics were crushed and premixed with other formulation components in a planetary mixer for 20 minutes.

[0068] The mixture was fed into a twin-screw extruder and melt-blended at 160-180°C with a screw speed of 140 rpm.

[0069] The carbon dioxide supercritical fluid plasticizing process is used with a pressure of 11MPa and a temperature of 38°C.

[0070] A low-temperature plasma surface treatment and grafting modification process was used, with a power of 120 W and a treatment time of 4 minutes, followed by grafting of fluorinated polymers.

[0071] Extrusion molding is used to make exterior wall material samples.

[0072] Enhancement Description:

[0073] The processing temperature dropped from 200°C to 170°C, a decrease of 15%. The carbon dioxide supercritical fluid plasticization process effectively lowered the processing temperature of PVC and reduced energy consumption.

[0074] The surface hardness of the material is increased from 2H to 3H, and the wear resistance is significantly improved. The low-temperature plasma surface treatment and grafting modification process introduces a fluorine-containing polymer molecular chain with higher hardness on the surface of the material, enhancing the surface performance.

[0075] Compared with the untreated material, the adhesion to the coating increased from 5N / cm to 12N / cm, an increase of 140%. The surface of the grafted modified material formed a stronger chemical bond and physical adsorption with the coating, which enhanced the adhesion.

[0076] In the flame retardant performance test, the limiting oxygen index increased from 26% to 32%. The waste liquid crystal display material fragments and the phosphorus-nitrogen-silicon-boron quaternary synergistic flame retardant work together to improve the flame retardant performance of the material.

[0077] In the flexibility test, the bending angle of the material increased from 120° to 150°. The biodegradable polyester polyol effectively improved the flexibility of the material.

[0078] Example 4

[0079] Recipe Implementation:

[0080] The base material is waste polypropylene (PP), which accounts for 70% of the mass.

[0081] Add 10% of waste carbon fiber and carbon nanotube composite reinforcement to enhance tensile strength and conductivity.

[0082] Adding 8% modified montmorillonite can improve the barrier properties and thermal stability of the material.

[0083] 6% of organic silicon-phosphorus flame retardant is mixed in to improve the flame retardant effect.

[0084] 6% cross-linkable rubber particles are introduced to improve the flexibility and impact resistance of the material.

[0085] Process implementation:

[0086] After the waste plastic is crushed, it is premixed with other formulation components in a high-speed mixer for 15 minutes.

[0087] The mixture was transferred to a twin-screw extruder and melt-blended at 170-190°C with a screw speed of 150 rpm.

[0088] During the blending process, an initiator is added through a side feeding device to initiate a crosslinking reaction of the crosslinkable rubber particles.

[0089] The hot pressing process was adopted and the pressure was maintained at 180℃ and 10MPa for 10 minutes to make the exterior wall material sample.

[0090] Enhancement Description:

[0091] The tensile strength increased from 35MPa to 50MPa, an increase of 42.9%. The composite reinforcement material of waste carbon fiber and carbon nanotubes is evenly dispersed in the PP matrix, forming an effective reinforcement network and enhancing the material's load-bearing capacity.

[0092] The volume resistivity of the material is reduced from 10^12Ω·cm to 10^9Ω·cm, and the conductivity is significantly improved. The synergistic effect of carbon nanotubes and carbon fibers builds a conductive path inside the material, giving the material a certain degree of conductivity.

[0093] In the thermogravimetric analysis test, the initial decomposition temperature increased from 300°C to 320°C, and the thermal stability was enhanced. The lamellar structure of the modified montmorillonite played a physical barrier role in the material, delaying the thermal decomposition process of the material.

[0094] In the UL-94 vertical combustion test, the flame retardant level was upgraded from no flame retardancy to V-2 level. During the combustion process, the organic silicon-phosphorus flame retardant forms a silicon-phosphorus composite carbon layer with heat insulation and flame retardancy, which effectively inhibits the spread of flames.

[0095] Impact strength from 20kJ / m 2 Increased to 30 kJ / m 2 , increased by 50%. After cross-linking, the cross-linkable rubber particles form an elastic network structure, which effectively absorbs and disperses impact energy and enhances the toughness of the material.

[0096] Example 5

[0097] Recipe Implementation:

[0098] The base material is a mixture of waste polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) in a mass ratio of 3:2.

[0099] Adding 12% of waste glass fiber and graphene oxide composite reinforcement improves tensile strength and thermal stability.

[0100] 10% of magnesium hydroxide-aluminum hydroxide compound flame retardant is added to enhance the flame retardant performance.

[0101] Mixing 5% of hyperbranched epoxy resin can improve the flexibility and adhesion of the material.

[0102] 3% of light stabilizer is introduced to improve the weather resistance of the material.

[0103] Process implementation:

[0104] First, the waste plastics are mixed and crushed, and premixed with other formulation components in a high-speed mixer for 10 minutes.

[0105] Enter into the twin-screw extruder, melt blend at 240-260°C, and the screw speed is 160rpm.

[0106] The injection molding process is used to inject the material into the mold for molding.

[0107] The formed material is post-treated under UV light to activate the light stabilizer.

[0108] Enhancement Description:

[0109] The tensile strength increased from 45MPa to 60MPa, an increase of 33.3%. The composite reinforcement of waste glass fiber and graphene oxide formed a good interface with the PET and PBT matrix, enhancing the tensile properties of the material.

[0110] In the thermal stability test, the mass retention rate of the material at 350°C increased from 50% to 65%. The high thermal conductivity and barrier properties of graphene oxide and the reinforcement of waste glass fiber effectively improved the thermal stability of the material.

[0111] The limiting oxygen index increased from 28% to 32%. The magnesium hydroxide-aluminum hydroxide compound flame retardant absorbs a large amount of heat when it is thermally decomposed, and the released water vapor and carbon dioxide and other gases dilute the concentration of combustible gases, thereby improving the flame retardant properties of the material.

[0112] The adhesion between the material and the coating increased from 3N / cm to 8N / cm, an increase of 166.7%. The special molecular structure of the hyperbranched epoxy resin enables it to form strong chemical bonds and physical adsorption with the PET and PBT matrix and coating materials, thus enhancing the adhesion.

[0113] In the artificial accelerated aging test, after 1,000 hours of ultraviolet irradiation, the mechanical property retention rate of the material increased from 60% to 75%. The light stabilizer effectively inhibited the degradation of the material by ultraviolet rays and improved the weather resistance of the material.

[0114] Example 6

[0115] Recipe Implementation:

[0116] The base material is waste polymethyl methacrylate (PMMA), accounting for 75% of the mass.

[0117] Add 10% of the composite additive of waste cellulose fiber and nano-silicon dioxide to enhance the mechanical properties and water resistance.

[0118] Add 8% intumescent flame retardant to improve flame retardant properties.

[0119] 5% of organic titanate coupling agent is mixed in to improve the interface compatibility of the material.

[0120] 2% of mildewcide is introduced to give the material mildew-resistant properties.

[0121] Process implementation:

[0122] The waste plastics were crushed and premixed with other formulation components in a planetary mixer for 20 minutes.

[0123] The mixture was fed into a twin-screw extruder and melt-blended at 160-180°C with a screw speed of 140 rpm.

[0124] The extrusion molding process is used to extrude the material into the desired shape.

[0125] The molded material was pretreated in an environment with a humidity of 80% and a temperature of 30°C before the mildew resistance test.

[0126] Enhancement Description:

[0127] The bending strength increased from 50MPa to 65MPa, an increase of 30%. The composite additive of waste cellulose fiber and nano-silicon dioxide played a reinforcing role in the PMMA matrix and improved the bending performance of the material.

[0128] After being immersed in water for 7 days, the water absorption rate of the material was reduced from 10% to 5%. The hydrophobic properties of nano-silica and its synergistic effect with waste cellulose fibers effectively reduced the water absorption rate of the material and improved its water resistance.

[0129] In the UL-94 vertical combustion test, it reaches the V-0 flame retardant grade. When heated, the intumescent flame retardant forms an intumescent carbon layer, which effectively blocks the transfer of heat and oxygen and improves the flame retardant properties of the material.

[0130] Compared with the material without organic titanate coupling agent, the tensile strength of the material is increased by 8%. The organic titanate coupling agent improves the interfacial compatibility between the components, allowing the material to transfer stress more effectively when subjected to force.

[0131] In the anti-mildew performance test, after 28 days of cultivation, a large amount of mold growth appeared on the surface of the material without the addition of anti-mildew agent, while the growth of mold on the surface of the material with the addition of anti-mildew agent was significantly inhibited, with almost no visible mold. The anti-mildew agent effectively inhibited the growth and reproduction of mold, giving the material good anti-mildew performance.

[0132] Example 7

[0133] Recipe Implementation:

[0134] Waste polyvinyl chloride (PVC) is used as the base material, accounting for 70%.

[0135] The composite reinforcement material of 12% waste polyphenylene sulfide (PPS) fiber and nano calcium carbonate is added to enhance the hardness and tensile strength of the material.

[0136] Add 8% of organic phosphorus-nitrogen flame retardant to improve flame retardant properties.

[0137] 6% maleic anhydride grafted polyethylene (PE-g-MAH) was mixed in as a compatibilizer to improve the compatibility between different plastics.

[0138] A composite antibacterial agent of 4% nano zinc oxide and cerium dioxide is introduced to give the material antibacterial properties.

[0139] Process implementation:

[0140] After the waste PVC is crushed, it is premixed with other formulation components in a high-speed mixer for 15 minutes.

[0141] The mixture was put into a twin-screw extruder and melt-blended at 160-180°C with a screw speed of 150 rpm.

[0142] During the blending process, the water and volatiles in the system are removed by a vacuum device.

[0143] The compression molding process was adopted and the pressure was maintained at 170℃ and 12MPa for 12 minutes to make the exterior wall material sample.

[0144] Enhancement Description:

[0145] The hardness is increased from Shore D60 to Shore D70, an increase of about 16.7%. The high strength of the waste PPS fiber and the rigid filling effect of nano-calcium carbonate significantly increase the hardness of the material.

[0146] The tensile strength increased from 38MPa to 52MPa, an increase of 36.8%. The composite reinforcement material of waste PPS fiber and nano-calcium carbonate forms a stable reinforcement skeleton in the PVC matrix, enhancing the material's bearing capacity.

[0147] In the UL-94 vertical combustion test, it was upgraded from V-2 to V-0. When the organic phosphorus-nitrogen flame retardant burns, the phosphorus and nitrogen elements work together to form an efficient flame retardant barrier, effectively inhibiting the spread of flames.

[0148] Compared with the material without the addition of compatibilizer PE-g-MAH, the impact strength of the material increased by 12%. PE-g-MAH improves the compatibility of PVC with other components, reduces interface defects and improves the toughness of the material.

[0149] In the antibacterial test, the antibacterial rate against Escherichia coli and Staphylococcus aureus reached more than 95%. The composite antibacterial agent of nano zinc oxide and cerium dioxide effectively inhibited the growth and reproduction of bacteria by releasing active oxygen species and metal ions.

[0150] Example 8

[0151] Recipe Implementation:

[0152] The base material is a mixture of waste polycarbonate (PC) and polyamide (PA) in a mass ratio of 4:6.

[0153] Add 10% of the composite reinforcement of waste aramid fiber and carbon nanotubes to enhance the tensile and bending properties.

[0154] 10% of aluminum hydroxide-zinc borate compound flame retardant is added to improve the flame retardant performance.

[0155] 5% of hydroxyl-terminated liquid nitrile rubber (HTBN) is mixed in as a toughening agent to improve the impact resistance of the material.

[0156] A 5% compound system of ultraviolet absorber and hindered amine light stabilizer is introduced to enhance the weather resistance of the material.

[0157] Process implementation:

[0158] First, the waste plastics are mixed and crushed, and premixed with other formulation components in a high-speed mixer for 10 minutes.

[0159] Enter into the twin-screw extruder, melt blend at 230-250°C, and the screw speed is 160rpm.

[0160] During the blending process, the materials are ultrasonically treated by an ultrasonic device to promote uniform dispersion of the components.

[0161] The injection molding process is used to inject the material into the mold for molding.

[0162] The molded material is pretreated before aging testing in a simulated natural climate environment.

[0163] Enhancement Description:

[0164] The bending strength increased from 55MPa to 70MPa, an increase of 27.3%. The composite reinforcement of waste aramid fiber and carbon nanotubes formed a strengthening network in the PC and PA matrix, improving the bending bearing capacity of the material.

[0165] Impact strength from 25kJ / m 2 Increased to 35kJ / m 2 , increased by 40%. HTBN toughening agent forms an elastic phase inside the material, effectively absorbing and dispersing impact energy, and enhancing the toughness of the material.

[0166] The limiting oxygen index increased from 26% to 30%. When the aluminum hydroxide-zinc borate compound flame retardant is decomposed by heat, aluminum hydroxide releases water to cool down, and zinc borate promotes the formation of a carbon layer, synergistically improving the flame retardant performance.

[0167] In the weathering test, after 1500 hours of simulated natural weather aging, the mechanical property retention rate of the material increased from 55% to 70%. The compound system of UV absorber and hindered amine light stabilizer effectively absorbs and quenches UV energy, inhibiting the photo-oxidative degradation of the material.

[0168] The tensile strength of the material increased by 5% compared to the material without ultrasonic treatment. Ultrasonic treatment promotes uniform dispersion of the components, reduces stress concentration points, and improves the overall performance of the material.

[0169] Example 9

[0170] Recipe Implementation:

[0171] Waste polystyrene (PS) is used as the base material, accounting for 75%.

[0172] Add 8% of waste wood fiber and nano-titanium dioxide composite additives to enhance mechanical properties and light resistance.

[0173] Add 8% intumescent flame retardant to enhance the flame retardant effect.

[0174] Mix 5% of silane coupling agent to improve the interfacial bonding strength of the material.

[0175] 4% of phase change energy storage material is introduced to give the material the function of regulating temperature.

[0176] Process implementation:

[0177] The waste PS was crushed and premixed with other formulation components in a planetary mixer for 20 minutes.

[0178] The mixture was fed into a twin-screw extruder and melt-blended at 170-190°C with a screw speed of 140 rpm.

[0179] During the blending process, a static mixer is used to further promote uniform mixing of the materials.

[0180] The extrusion molding process is used to extrude the material into the desired shape.

[0181] The temperature regulation performance of the molded material is tested under different temperature environments.

[0182] Enhancement Description:

[0183] The tensile strength increased from 32MPa to 45MPa, an increase of 40.6%. The composite additive of waste wood fiber and nano-titanium dioxide plays a reinforcing role in the PS matrix, and nano-titanium dioxide can also improve the light stability of the material.

[0184] In the light resistance test, after 500 hours of ultraviolet irradiation, the yellowing index of the material decreased from 10 to 6. The shielding and photocatalytic effect of nano-titanium dioxide on ultraviolet rays effectively inhibited the photo-oxidative yellowing of PS.

[0185] In the UL-94 vertical burning test, it reaches the V-1 flame retardant grade. The carbon layer formed by the thermal expansion of the intumescent flame retardant effectively blocks heat and oxygen, improving the flame retardant performance.

[0186] Compared with the material without silane coupling agent, the bending strength of the material is increased by 10%. Silane coupling agent improves the interface bonding force between the components, making the stress transmission of the material more uniform when the material is subjected to force.

[0187] In the temperature regulation performance test, when the ambient temperature rises rapidly from 25°C to 35°C, the surface temperature of the material with phase change energy storage material added rises 2°C / min slower than that of the material without the addition, and the maximum temperature is 3°C lower. Phase change energy storage materials effectively regulate the temperature of the material by absorbing and releasing heat during the phase change process when the temperature changes.

[0188] Example 13

[0189] Design of new organic compound modifiers:

[0190] An organic compound named 5-(4-(4-cinnamoyloxybutoxy)-3-chlorophenyl)-2-(5-methoxy-3-pyridyl)-1,3,4-oxadiazole-5-thiol (CCMPOT) was designed. The design principle is based on the synergistic effect of different functional groups. In the waste plastic system, in the 5-(4-(4-cinnamoyloxybutoxy)-3-chlorophenyl) part, the cinnamoyl group of the cinnamoyloxybutoxy group can interact with the aromatic structure in the waste plastic through π-π stacking, thereby enhancing the intermolecular binding force. The presence of chlorine atoms optimizes the interaction between the phenyl group and other groups, while the butoxy group plays a role in connecting and regulating the electron cloud density. In the 2-(5-methoxy-3-pyridyl) part, the methoxy group enhances the stability of the pyridyl group, and the pyridyl group combines with other components through π-π stacking and hydrogen bonds to improve the compatibility of the material. In the structure of 1,3,4-oxadiazole-5-thiol, the thiol group can form strong chemical bonds with metal nanoparticles or other active groups to enhance the cross-linking degree of the material, and the conjugated structure of the oxadiazole ring helps to improve the thermal and chemical stability of the material.

[0191] Synthesis method:

[0192] 5-(4-(4-cinnamoyloxybutoxy)-3-chlorobenzoic acid) and 5-methoxy-3-pyridinecarboxylic acid hydrazide-5-thiol are used as raw materials. 5-(4-(4-cinnamoyloxybutoxy)-3-chlorobenzoic acid) and dichlorothionyl are reacted in anhydrous toluene with pyridine as a catalyst at 70°C for 3 hours to obtain the corresponding acid chloride. Then, the acid chloride is added dropwise to an anhydrous ethanol solution containing 5-methoxy-3-pyridinecarboxylic acid hydrazide-5-thiol and triethylamine, and the reaction is stirred at room temperature for 10 hours. After the reaction is completed, the solvent is removed by distillation under reduced pressure, and recrystallization is performed with ethyl acetate and petroleum ether to obtain the target product CCMPOT. This synthesis method refers to the preparation literature of oxadiazole thiol and pyridine compounds.

[0193] Material preparation:

[0194] The base material is waste polycarbonate (PC), accounting for 70%.

[0195] 10% CCMPOT was added as a modifier.

[0196] 10% of aluminum hydroxide (ATH) was added as a flame retardant.

[0197] 5% carbon fiber is mixed in as reinforcement.

[0198] 5% nano titanium dioxide (TiO2) is introduced to improve the weather resistance of the material.

[0199] After the waste PC is crushed, it is premixed with other formulation components in a high-speed mixer for 15 minutes.

[0200] Enter into the twin-screw extruder, melt blend at 220-240°C, and the screw speed is 180rpm.

[0201] The compression molding process was adopted and the pressure was maintained at 200℃ and 10MPa for 15 minutes to make the exterior wall material sample.

[0202] Synergistic test:

[0203] Compared with the same formula material without CCMPOT, the tensile strength of the material with CCMPOT increased by 15% to 68MPa. The synergy between the various groups of CCMPOT and the PC matrix and other additives enhances the internal structure of the material, making it perform better when subjected to tensile stress.

[0204] In the thermal stability test, the onset decomposition temperature increased by 18°C. The oxadiazole ring and thiol group synergize with ATH to effectively inhibit the decomposition of the material at high temperature.

[0205] Compared with the materials modified with common cinnamoyloxy and thiol compounds in the prior art, the tensile strength of the material of this embodiment is increased by 8%-12%, and the initial decomposition temperature is increased by 10-15°C. In the weather resistance test, after 1500 hours of artificial accelerated aging, the mechanical property retention rate of the material is 10%-15% higher than that of similar modified materials in the prior art, indicating that CCMPOT improves the weather resistance of the material.

[0206] Example 10

[0207] Recipe Implementation:

[0208] The base material is waste polyethersulfone (PES), accounting for 65%.

[0209] Adding 15% of the composite reinforcement phase of waste basalt fiber and metal organic framework (MOF) derived carbon nanosheets, the mechanical properties and thermal stability of the material are enhanced through the synergy of the two. Basalt fiber has high strength and modulus, which can provide basic mechanical support; MOF derived carbon nanosheets have a unique porous structure and large specific surface area, which can enhance the interface bonding with the base material, stabilize the structure at high temperature, and improve thermal stability.

[0210] Adding 10% of boron-silicon-phosphorus-nitrogen quaternary hybrid flame retardant, through the synergistic effect of boron, silicon, phosphorus and nitrogen elements in different stages and modes, high-efficiency flame retardancy is achieved. Boron promotes the formation of a glassy protective layer at high temperature, silicon enhances the strength of the carbon layer, phosphorus captures free radicals, and nitrogen dilutes combustible gases.

[0211] 5% polydimethylsiloxane (PDMS) grafted thermoplastic polyurethane (TPU) elastomer is mixed in, and the low surface energy of PDMS and the elasticity of TPU are utilized to improve the flexibility, water resistance and surface self-cleaning performance of the material.

[0212] By introducing 5% rare earth-doped titanium dioxide quantum dots, the special electronic structure of rare earth elements and the strong quantum confinement effect of titanium dioxide quantum dots are utilized to give the material the ability to photocatalytically degrade harmful gases and self-cleaning and antibacterial properties.

[0213] Process implementation:

[0214] After the waste PES is crushed, it is premixed with other formulation components in a high-speed mixer for 15 minutes to ensure that the components are initially dispersed evenly.

[0215] Enter the twin-screw extruder and melt blend at 280-300°C with a screw speed of 180rpm to ensure that all components are fully integrated at high temperature.

[0216] During the blending process, pulse electric field treatment was used with an electric field strength of 2 kV / cm and a pulse frequency of 15 Hz to promote the orientation arrangement and interface bonding of each component.

[0217] The compression molding process was adopted and the pressure was maintained at 250℃ and 15MPa for 15 minutes to make the exterior wall material sample.

[0218] The formed material is post-treated under ultraviolet light to stimulate the photocatalytic properties of the rare earth-doped titanium dioxide quantum dots.

[0219] Enhancement Description:

[0220] The tensile strength increased from 50MPa to 75MPa, an increase of 50%. The composite reinforcement phase of waste basalt fiber and MOF-derived carbon nanosheets forms a stable reinforcement network in the PES matrix, effectively bearing and transmitting stress.

[0221] The thermal stability is significantly improved, and thermogravimetric analysis shows that the mass retention rate at 400°C increases from 40% to 60%. The high temperature stability of MOF-derived carbon nanosheets and the synergistic effect of the boron-silicon-phosphorus-nitrogen quaternary hybrid flame retardant effectively inhibit the thermal decomposition of the material.

[0222] In the UL-94 vertical burning test, it goes directly from no flame retardancy to V-0. The multi-element synergistic flame retardant mechanism of the boron-silicon-phosphorus-nitrogen quaternary hybrid flame retardant forms an efficient flame retardant barrier.

[0223] The flexibility of the material is greatly improved, and the elongation at break is increased from 10% to 20%. The PDMS-grafted TPU elastomer forms an elastic network inside the material, increasing the activity space of the molecular chain.

[0224] In the water resistance test, the water absorption rate of the material after immersion in water for 10 days was reduced from 8% to 3%. The low surface energy of PDMS makes the surface of the material hydrophobic, reducing the absorption of water.

[0225] In the photocatalytic performance test, the degradation rate of formaldehyde reached 80% within 24 hours. Rare earth-doped titanium dioxide quantum dots produce strong oxidizing free radicals under ultraviolet light, effectively decomposing harmful gases such as formaldehyde.

[0226] In the antibacterial test, the antibacterial rates against Escherichia coli and Staphylococcus aureus reached more than 98%. The active oxygen species produced by the photocatalytic action of rare earth-doped titanium dioxide quantum dots have strong antibacterial ability.

[0227] Embodiment 11

[0228] Recipe Implementation:

[0229] The base material is a mixture of waste polylactic acid (PLA) and polyhydroxyalkanoate (PHA) in a mass ratio of 3:2, making full use of their biodegradability and good processing properties.

[0230] By adding 12% of waste silk fiber and graphene aerogel composite reinforcement, the high strength and flexibility of silk fiber and the high specific surface area and excellent mechanical properties of graphene aerogel work together to enhance the comprehensive mechanical properties of the material.

[0231] 10% of phosphorus-nitrogen flame retardant based on plant polyphenols is added to improve the flame retardant properties by utilizing the rich active groups of plant polyphenols and the synergistic flame retardant effect of phosphorus-nitrogen elements, while giving the material certain antioxidant properties.

[0232] 8% of nano-silica modified with hyperbranched polyamide-amine (PAMAM) is mixed in, and the dispersibility, mechanical properties and heat resistance of the material are improved through the synergy between the hyperbranched PAMAM and the nano-silica.

[0233] The introduction of 2% polynorbornene microspheres with shape memory function gives the material self-healing ability.

[0234] Process implementation:

[0235] First, the waste plastics were mixed and crushed, and then premixed with other formulation components in a planetary mixer for 20 minutes to achieve uniform mixing.

[0236] Enter the twin-screw extruder and melt blend at 160-180°C with a screw speed of 150rpm to ensure that all components are evenly dispersed at a suitable temperature.

[0237] During the blending process, carbon dioxide supercritical fluid is introduced at a pressure of 10 MPa and a temperature of 35°C to improve the fluidity and mixing uniformity of the materials.

[0238] The injection molding process is used to inject the material into the mold for molding.

[0239] The molded material undergoes shape memory activation under specific temperature and stress conditions.

[0240] Enhancement Description:

[0241] The bending strength increased from 45MPa to 65MPa, an increase of about 44.4%. The composite reinforcement of waste silk fiber and graphene aerogel forms an effective reinforcement structure in the PLA and PHA matrix, improving the bending bearing capacity.

[0242] The limiting oxygen index is increased from 24% to 30%. During the combustion process, the phosphorus-nitrogen flame retardant based on plant polyphenols improves the flame retardant performance through the carbonization of plant polyphenols and the gas phase and condensed phase flame retardant effect of phosphorus-nitrogen elements.

[0243] The antioxidant properties of the material were significantly improved. In the accelerated oxidation test, the oxidation induction time was extended from 30 minutes to 60 minutes. The antioxidant activity of plant polyphenols effectively inhibited the oxidative degradation of the material.

[0244] Compared with the material without adding the nano-silica modified by hyperbranched polyamidoamine (PAMAM), the tensile strength of the material is increased by 8%. The nano-silica modified by PAMAM is evenly dispersed in the material and enhances the interface bonding with the matrix.

[0245] In the shape memory test, when the material was bent and deformed, it was heated at 60°C for 5 minutes, and the shape recovery rate of the material reached 90%. The polynorbornene microspheres with shape memory function restored their original shape under temperature stimulation, driving the overall recovery of the material.

[0246] In the biodegradation test, the mass loss rate increased from 20% to 30% after burial in soil for 4 months. The biodegradability of PLA and PHA and the natural degradability of waste silk fibers synergistically promoted the biodegradation of the materials in the composite system.

[0247] Example 12

[0248] Recipe Implementation:

[0249] The base material is a mixture of waste polystyrene (PS) and polymethyl methacrylate (PMMA) in a mass ratio of 2:3, combining the advantages of both, such as the rigidity of PS and the transparency of PMMA.

[0250] A composite reinforcement material of 10% waste glass fiber and aluminum nitride (AlN) nanowires is added. The glass fiber provides high strength, and the aluminum nitride nanowires have good thermal conductivity and reinforcement, thereby improving the mechanical properties and thermal management properties of the material.

[0251] 8% of silicon-aluminum-boron-magnesium quaternary synergistic flame retardant is added to form a stable flame retardant protective layer at high temperature through the synergistic effect of silicon, aluminum, boron and magnesium elements.

[0252] 6% of propylene oxide-ethylene oxide block copolymer (PEO-PPO-PEO) is mixed as a toughening agent to improve the flexibility and impact resistance of the material.

[0253] The introduction of a composite system of 6% photochromic organic small molecules and silica nanoparticles gives the material photochromic properties and can adjust indoor light.

[0254] Process implementation:

[0255] After the waste plastic is crushed, it is premixed with other formulation components in a high-speed mixer for 15 minutes.

[0256] The mixture was put into a twin-screw extruder and melt-blended at 170-190°C with a screw speed of 160 rpm.

[0257] During the blending process, ultrasonic and microwave combined treatment was used, with the ultrasonic power being 200W and the microwave power being 500W, to promote the dispersion and chemical reaction of each component.

[0258] The exterior wall material sample was made by extrusion-blow molding process.

[0259] The photochromic performance of the molded material was tested under different light intensities.

[0260] Enhancement Description:

[0261] The tensile strength increased from 35MPa to 50MPa, an increase of 42.9%. The composite reinforcement material of waste glass fiber and aluminum nitride (AlN) nanowires formed a stable reinforcement skeleton in the PS and PMMA matrix, enhancing the load-bearing capacity.

[0262] The thermal conductivity of the material increased from 0.1W / (m·K) to 0.15W / (m·K), improving thermal management performance. The high thermal conductivity of aluminum nitride nanowires forms heat conduction channels in the material.

[0263] In the UL-94 vertical combustion test, it is upgraded from V-2 to V-0. The silicon-aluminum-boron-magnesium quaternary synergistic flame retardant forms an efficient flame retardant barrier during combustion, effectively inhibiting the spread of flames.

[0264] Impact strength from 20kJ / m2 Increased to 30 kJ / m 2 , increased by 50%. Propylene oxide-ethylene oxide block copolymer (PEO-PPO-PEO) forms an elastic area inside the material, effectively absorbing impact energy.

[0265] In the photochromic performance test, when the light intensity increases from 500 lux to 2000 lux, the light transmittance of the material decreases from 80% to 50%. The composite system of photochromic organic small molecules and silica nanoparticles undergoes structural changes under light, achieving photochromism and effectively adjusting light transmittance.

[0266] Compared with the material without ultrasonic and microwave treatment, the bending strength of the material increased by 6%. The ultrasonic and microwave treatment promoted the uniform dispersion and interface bonding of the components and improved the overall performance of the material.

[0267] Embodiment 14

[0268] Design of new organic compound modifiers:

[0269] An organic compound called 3-(4-(3-methacryloyloxypropoxy)-3-fluorophenyl)-5-(2-quinolyl)-1,2,4-triazole-5-thione (MFPQT) was developed. The design principle is to use the characteristics of different functional groups to improve the performance of waste plastics. In the waste plastic system, in the 3-(4-(3-methacryloyloxypropoxy)-3-fluorophenyl) part, the double bond in the methacryloxypropoxy group can undergo an addition reaction with the unsaturated bond in the waste plastic to achieve effective bonding with the base material. The fluorine atom optimizes the interaction between the phenyl group and other groups, and the propoxy group adjusts the steric hindrance and electron cloud density. In the 5-(2-quinolyl) part, the quinolyl group has a larger conjugated system, which is tightly combined with other components through π-π stacking and hydrogen bonding, thereby improving the compatibility of the material. In the structure of 1,2,4-triazole-5-thione, the thione group can form a coordination bond with metal ions to enhance the cross-linking degree of the material, and the conjugated structure of the triazole ring helps to improve the thermal stability and flame retardant properties of the material.

[0270] Synthesis method:

[0271] 3-(4-(3-methacryloyloxypropoxy)-3-fluorobenzoic acid) and 2-quinolinecarboxylic acid hydrazide-5-thione are used as raw materials. 3-(4-(3-methacryloyloxypropoxy)-3-fluorobenzoic acid) is mixed with dicyclohexylcarbodiimide (DCC) and 4-dimethylaminopyridine (DMAP) in anhydrous dichloromethane and stirred at room temperature for 30 minutes to activate the carboxyl group. Then 2-quinolinecarboxylic acid hydrazide-5-thione is added and the reaction is continued to stir at room temperature for 12 hours. After the reaction is completed, the precipitate is filtered out, the solvent is removed by vacuum distillation, and the target product MFPQT is obtained by recrystallization with n-hexane and ethyl acetate. This synthesis method refers to the preparation literature of triazolethione and quinoline compounds.

[0272] Material preparation:

[0273] The base material is waste polypropylene (PP) and polyethylene (PE) mixed plastics (mass ratio 3:2), accounting for 75%.

[0274] 8% MFPQT was added as a modifier.

[0275] 10% melamine cyanurate (MCA) was added as a flame retardant.

[0276] 5% glass fiber is mixed in as reinforcement.

[0277] The introduction of 2% antioxidant 1010 can improve the anti-oxidation performance of the material.

[0278] After the waste plastic is crushed, it is premixed with other formulation components in a high-speed mixer for 15 minutes.

[0279] Enter into the twin-screw extruder, melt blend at 170-190°C, and the screw speed is 160rpm.

[0280] The injection molding process is used to make the exterior wall material sample.

[0281] Synergistic test:

[0282] Compared with the same formula material without MFPQT, the flexural modulus of the material with MFPQT increased by 18% to 3.7GPa. MFPQT works synergistically with glass fiber to enhance the rigidity of the material, making it perform better when subjected to bending stress.

[0283] In the flame retardant performance test, the limiting oxygen index increased from 26% to 31%. The triazole ring and thioketone group of MFPQT synergistically with MCA to form a more stable flame retardant system at high temperatures.

[0284] Compared with the materials modified with common methacryloyloxy and thioketone compounds in the prior art, the bending modulus of the material of this embodiment is increased by 7%-13%, and the limiting oxygen index is increased by 2-4 percentage points. In the oxidation resistance test, the oxidation induction time of the material under accelerated oxidation conditions is extended by 15-20 minutes compared with similar modified materials in the prior art, indicating that MFPQT improves the oxidation resistance of the material.

[0285] Embodiment 15

[0286] Design of new organic compound modifiers:

[0287] An organic compound named 4-(2-(4-succinyloxybutoxy)-3-bromophenyl)-3-(5-methyl-2-pyrimidinyl)-1,2,4-oxadiazole-5-thioether (SBPOT) was designed. The design idea is to optimize the performance of waste plastics through the combination of different functional groups. In the waste plastic system, in the 4-(2-(4-succinyloxybutoxy)-3-bromophenyl) part, the succinyl group of the succinyloxybutoxy group can form hydrogen bonds with hydroxyl groups or amino groups in the waste plastics to enhance the intermolecular force. The bromine atom optimizes the interaction between the phenyl group and other groups, and the butoxy group regulates the electron cloud density and the connection effect. In the 3-(5-methyl-2-pyrimidinyl) part, the methyl group enhances the stability of the pyrimidinyl group, and the pyrimidinyl group combines with other components through π-π stacking and hydrogen bonds to improve the compatibility of the material. In the 1,2,4-oxadiazole-5-sulfide structure, the sulfide group can form a strong chemical bond with the metal oxide to enhance the cross-linking degree of the material, and the conjugated structure of the oxadiazole ring helps to improve the thermal stability and chemical stability of the material.

[0288] Synthesis method:

[0289] 4-(2-(4-succinyloxybutoxy)-3-bromobenzoic acid) and 5-methyl-2-pyrimidinecarboxylic acid hydrazide-5-sulfide are used as raw materials. 4-(2-(4-succinyloxybutoxy)-3-bromobenzoic acid) is reacted with dichlorothionyl in anhydrous toluene and refluxed at 65°C for 2 hours to obtain the corresponding acid chloride. Then the acid chloride is added dropwise to an anhydrous ethanol solution containing 5-methyl-2-pyrimidinecarboxylic acid hydrazide-5-sulfide and triethylamine, and the reaction is stirred at room temperature for 10 hours. After the reaction is completed, the solvent is removed by distillation under reduced pressure, and recrystallization is carried out with ethyl acetate and petroleum ether to obtain the target product SBPOT. This synthesis method refers to the preparation process of similar compounds containing oxadiazole sulfide and pyrimidine.

[0290] Material preparation:

[0291] Waste polyvinyl chloride (PVC) is used as the base material, accounting for 70%.

[0292] 10% SBPOT was added as a modifier.

[0293] 12% magnesium hydroxide (MH) was added as a flame retardant.

[0294] 8% aramid fiber is mixed in as a reinforcement.

[0295] 2% of UV absorber UV-531 is introduced to improve the weather resistance of the material.

[0296] After the waste PVC is crushed, it is premixed with other formulation components in a high-speed mixer for 15 minutes.

[0297] Enter into the twin-screw extruder, melt blend at 160-180°C, and the screw speed is 150rpm.

[0298] The exterior wall material sample is made by extrusion molding technology.

[0299] Synergistic test:

[0300] Compared with the same formula material without SBPOT, the tensile strength of the material with SBPOT increased by 16% to 48MPa. SBPOT and aramid fiber synergistically strengthened the internal structure of the material and improved the tensile properties of the material.

[0301] In the flame retardant performance test, the UL-94 vertical burning test was upgraded from V-2 to V-0. The oxadiazole ring and thioether group of SBPOT synergize with MH to form a more effective flame retardant barrier during combustion.

[0302] Compared with the materials modified with common succinyloxy and thioether compounds in the prior art, the tensile strength of the material in this embodiment is increased by 9%-13%, and in the UL-94 vertical burning test, it is improved from V-2 to V-0. In the weather resistance test, after 1000 hours of artificial accelerated aging, the color change △E of the material is 1.5 less than that of similar modified materials in the prior art, indicating that SBPOT improves the weather resistance of the material.

[0303] Example 16

[0304] Design of new organic compound modifiers:

[0305] An organic compound called 5-(3-(3-itaconimidoethoxy)-4-iodophenyl)-2-(5-fluoro-3-pyrazolyl)-1,3,4-thiadiazole-5-thione (IIPFT) was developed. The design principle is based on the optimization of the performance of waste plastics by different functional groups. In the waste plastic system, in the 5-(3-(3-itaconimidoethoxy)-4-iodophenyl) part, the double bond in the itaconimidoethoxy group can undergo an addition reaction with the unsaturated bond in the waste plastic to achieve effective bonding with the base material. The iodine atom optimizes the interaction between the phenyl group and other groups, and the ethoxy group adjusts the electron cloud density and steric hindrance. In the 2-(5-fluoro-3-pyrazolyl) part, the fluorine atom enhances the electron-withdrawing ability of the pyrazolyl group, and the pyrazolyl group combines with other components through π-π stacking and hydrogen bonds to improve the compatibility of the material. In the structure of 1,3,4-thiadiazole-5-thione, the thione group can form a coordination bond with metal ions to enhance the cross-linking degree of the material, and the conjugated structure of the thiadiazole ring helps to improve the thermal stability and flame retardant properties of the material.

[0306] Synthesis method:

[0307] 5-(3-(3-itaconyliminoethoxy)-4-iodobenzoic acid) and 5-fluoro-3-pyrazolecarboxylic acid hydrazide-5-thione are used as raw materials. 5-(3-(3-itaconyliminoethoxy)-4-iodobenzoic acid) is mixed with N,N-dicyclohexylcarbodiimide (DCC) and 4-dimethylaminopyridine (DMAP) in anhydrous dichloromethane and stirred at room temperature for 30 minutes to activate the carboxyl group. Then 5-fluoro-3-pyrazolecarboxylic acid hydrazide-5-thione is added and the reaction is continued to stir at room temperature for 12 hours. After the reaction is completed, the precipitate is removed by filtration, the solvent is removed by distillation under reduced pressure, and the target product IIPFT is obtained by recrystallization with n-hexane and ethyl acetate. This synthesis method refers to the preparation literature of thiadiazolethione and pyrazolyl compounds.

[0308] Material preparation:

[0309] The base material is a mixed plastic of waste polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) (mass ratio 1:1), accounting for 70%.

[0310] 10% IIPFT was added as a modifier.

[0311] 10% red phosphorus (RP) was added as a flame retardant.

[0312] 8% carbon fiber is mixed in as reinforcement.

[0313] 2% of UV-327 is introduced to improve the weather resistance of the material.

[0314] After the waste plastic is crushed, it is premixed with other formulation components in a high-speed mixer for 15 minutes.

[0315] Enter into the twin-screw extruder, melt blend at 250-270°C, and the screw speed is 170rpm.

[0316] The injection molding process is used to make the exterior wall material sample.

[0317] Synergistic test:

[0318] Compared with the same formula material without IIPFT, the impact strength of the material with IIPFT increased by 22% to 35kJ / m 2 IIPFT works in synergy with carbon fiber to enhance the toughness of the material, allowing it to better absorb energy when subjected to impact.

[0319] In the thermal stability test, the onset decomposition temperature increased by 20°C. The thiadiazole ring and thioketone group of IIPFT synergize with RP to effectively inhibit the decomposition of the material at high temperature.

[0320] Compared with the materials modified with common itaconimide-containing and thioketone compounds in the prior art, the impact strength of the material of this embodiment is increased by 10%-16%, and the initial decomposition temperature is increased by 12-18° C. In the weather resistance test, after 2000 hours of artificial accelerated aging, the mechanical property retention rate of the material is 12%-18% higher than that of similar modified materials in the prior art, indicating that IIPFT improves the weather resistance of the material.

[0321] Embodiment 17

[0322] Recipe Implementation:

[0323] The base material is waste polybutylene terephthalate (PBT), accounting for 60%.

[0324] By adding 15% of waste carbon fiber and boron nitride nanotube composite reinforcement materials, the high strength of carbon fiber and the excellent thermal conductivity and insulation properties of boron nitride nanotubes are utilized to improve the mechanical properties and thermal management capabilities of the material.

[0325] Add 10% of the composite flame retardant of modified lignin and magnesium hydroxide. The modified lignin not only has a certain flame retardancy, but also enhances the compatibility with the base material. The magnesium hydroxide decomposes under heat to absorb heat and release water vapor, which plays a role in flame retardancy and cooling.

[0326] 8% polyetheramine grafted ethylene-vinyl acetate copolymer (EVA-g-PEPA) is mixed to improve the flexibility and impact resistance of the material, while the active groups of the polyetheramine help to increase the degree of cross-linking of the material.

[0327] The introduction of 7% nano zirconium dioxide and cerium oxide composite powder improves the material's weather resistance and oxidation resistance, and stabilizes the material structure under ultraviolet and high temperature environments.

[0328] Process implementation:

[0329] After the waste PBT is crushed, it is premixed with other formulation components in a high-speed mixer for 20 minutes to ensure that the components are initially mixed evenly.

[0330] Enter the twin-screw extruder and melt blend at 230-250°C with a screw speed of 170rpm to ensure that all components are fully integrated at high temperature.

[0331] During the blending process, the dynamic vulcanization process is used to make EVA-g-PEPA undergo a cross-linking reaction under specific conditions to form a stable elastic network structure.

[0332] The compression molding process was adopted and the pressure was maintained at 220℃ and 12MPa for 15 minutes to make the exterior wall material sample.

[0333] The molded material is pre-treated for weather resistance in a UV aging box to simulate the lighting conditions in the actual use environment.

[0334] Enhancement Description:

[0335] The tensile strength increased from 45MPa to 70MPa, an increase of about 55.6%. The composite reinforcement material of waste carbon fiber and boron nitride nanotubes forms a stable reinforcement skeleton in the PBT matrix, effectively bearing and transmitting stress, and significantly enhancing the tensile properties of the material.

[0336] Thermal conductivity is increased from 0.2W / (m·K) to 0.3W / (m·K), improving thermal management performance. The high thermal conductivity of boron nitride nanotubes forms heat conduction channels in the material, which helps to quickly transfer and evenly distribute heat and avoid local overheating.

[0337] In the UL-94 vertical combustion test, the flame retardant level was improved from no flame retardancy to V-2 level. During the combustion process of the composite flame retardant of modified lignin and magnesium hydroxide, the modified lignin promotes the formation of the carbon layer, and the magnesium hydroxide decomposes to absorb heat and release water vapor to dilute the combustible gas, which together play a flame retardant role.

[0338] Impact strength from 22kJ / m 2 Increased to 35kJ / m 2 , an increase of about 59.1%. The elastic network structure formed by EVA-g-PEPA grafted with polyetheramine effectively absorbs and disperses impact energy, enhances the toughness of the material, and enables it to better resist damage when impacted.

[0339] In the weather resistance test, after 1,000 hours of ultraviolet irradiation, the mechanical property retention rate of the material increased from 50% to 70%. The composite powder of nano zirconium dioxide and cerium oxide effectively inhibits the degradation of the material by ultraviolet rays, improves the material's antioxidant properties, and stabilizes the material's structure and performance.

[0340] Compared with materials that do not use dynamic vulcanization, the flexibility of the material is improved, and the elongation at break is increased from 15% to 25%. The dynamic vulcanization process cross-links EVA-g-PEPA to form an elastic network, which increases the activity space of the molecular chain and improves the flexibility of the material.

[0341] Embodiment 18

[0342] The structure, composition and properties of the material are confirmed through a variety of analytical techniques. FT-IR spectroscopy can accurately identify characteristic functional groups in compounds. For example, in the examples, the specific absorption peaks of new organic compounds can verify their structural composition. 1 HNMR further determines the environment and quantity of hydrogen atoms in the molecule through chemical shift and peak area, and assists in clarifying the structure of the compound. Elemental analysis gives the proportion of each element in a quantitative form to ensure that the synthetic product meets expectations. These technologies confirm each other and ensure from different angles that the newly synthesized modifiers and recycled materials have accurate chemical structures and synergistic effects, as shown in Tables 1 and 2.

[0343]

[0344]

[0345] Table 2 Comparison of synergy

[0346]

[0347]

[0348]

[0349]

[0350]

[0351]

[0352]

[0353]

[0354]

[0355]

Claims

1. A method for preparing exterior wall flame retardant materials from waste plastics, characterized in that: The invention uses a mixed plastic of discarded polystyrene (PS) and polycarbonate (PC) as a base material, wherein in 80-100 parts by weight of the mixed plastic, the weight ratio of PS to PC is 3:2; the invention also comprises 5-10 parts by weight of discarded liquid crystal display material fragments, 8-10 parts by weight of bio-based degradable polyester polyol, 3-5 parts by weight of nano silicon carbide and boron nitride composite powder, 4-6 parts by weight of a phosphorus-nitrogen-silicon-boron quaternary synergistic flame retardant, 6-8 parts by weight of a composite reinforcement of discarded basalt fiber and graphene, 2-5 parts by weight of a composite material of photocatalytic nano titanium dioxide and activated carbon, 5-8 parts by weight of a hyperbranched polymer, and 0.5-1 parts by weight of an intelligent shape memory polymer microcapsule.

2. The formula for preparing exterior wall flame retardant material from waste plastics according to claim 1, characterized in that: The particle size of the waste liquid crystal display material fragments is micron-level, and they are obtained by crushing the waste liquid crystal display materials.

3. The formula for preparing exterior wall flame retardant material from waste plastics according to claim 1, characterized in that: The bio-based degradable polyester polyol is synthesized using biomass as raw material and is used to improve the flexibility and biodegradability of materials.

4. The formula for preparing exterior wall flame retardant material from waste plastics according to claim 1, characterized in that: In the nano-silicon carbide and boron nitride composite powder, the weight ratio of nano-silicon carbide to boron nitride is 2:

1.

5. A process for preparing exterior wall flame retardant materials from waste plastics, characterized in that: This includes washing, drying and crushing waste plastics; Add all components except smart shape memory polymer microcapsules into a high-speed mixer and premix at 80-100°C for 15 minutes; The mixed material is transferred to a twin-screw extruder and melt-blended at 180-220°C with a screw speed of 150-180 rpm; During the blending process, the smart shape memory polymer microcapsules were added through a side feeding device and the blending was continued for 5 minutes; The blended materials were treated at a microwave power of 600-800 W for 3-5 minutes using a microwave-assisted chemical cross-linking process; Using the carbon dioxide supercritical fluid plasticizing process, supercritical carbon dioxide is injected into the material at a pressure of 10-12MPa and a temperature of 35-40°C; The magnetic field assisted orientation molding process is used, and a magnetic field of 0.5-1T is applied during the injection molding process; The formed material is subjected to low-temperature plasma surface treatment and grafting modification process, treated in a plasma environment with a power of 100-150W for 3-5 minutes, and then subjected to grafting modification reaction.

6. A method for recycling waste plastics, characterized in that: Includes the following: Selection and use of new organic compound modifiers: For different types of waste plastics, organic compound modifiers with specific structures are selected. The modifiers react chemically with the corresponding waste plastics through their unique functional groups to improve the material properties. The details are as follows: When the waste plastic is a mixed plastic of polypropylene (PP) and polyethylene (PE) (mass ratio 3:2), 3-(4-(3-methacryloxypropoxy)-3-fluorophenyl)-5-(2-quinolyl)-1,2,4-triazole-5-thione (MFPQT) is used as a modifier; When the waste plastic is polyvinyl chloride (PVC), 4-(2-(4-succinyloxybutoxy)-3-bromophenyl)-3-(5-methyl-2-pyrimidinyl)-1,2,4-oxadiazole-5-thioether (SBPOT) is used as a modifier; When the waste plastic is a mixed plastic of polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) (mass ratio 1:1), 5-(3-(3-itaconimidoethoxy)-4-iodophenyl)-2-(5-fluoro-3-pyrazolyl)-1,3,4-thiadiazole-5-thione (IIPFT) is used as a modifier; When the waste plastic is polybutylene terephthalate (PBT), a composite reinforcement material of waste carbon fiber and boron nitride nanotubes is used as a modified reinforcement component; When the waste plastic is polymethyl methacrylate (PMMA), methyl 2-(acryloyloxy)benzoate (ABM) is used as a modifier; When the waste plastic is polyoxymethylene (POM), ethyl 3-(vinyloxy)benzoate (VOBAE) is used as a modifier; When the waste plastic is polylactic acid (PLA), 4-(methacryloyloxy)propyl benzoate (MAPBP) is used as a modifier; When the waste plastic is polyurethane (PU), 3-(acryloyloxy-2-methoxy)butyl benzoate (APMBB) is used as a modifier; When the waste plastic is a mixed plastic of polycarbonate (PC) and polyethylene terephthalate (PET), 4-(vinyl-3-acryloyloxy)benzoic acid isobutyl ester (VAPBIB) is used as a modifier; When the waste plastic is polystyrene (PS), 3-(2-methyl-3-acryloyloxypropoxy)benzoic acid (MAPBA) is used as a modifier; When the waste plastic is polypropylene (PP), 4-(3-butenoyloxy-2-methoxypropoxy)phenylacetic acid (BMOPA) is used as a modifier; When the waste plastic is polyvinyl chloride (PVC), 3-(2-vinyl-3-acryloyloxy) methyl benzoate (VAPMB) is used as a modifier; When the waste plastic is a mixed plastic of polypropylene (PP) and polyethylene (PE), 3-(2-methyl-3-butenoyloxy)propyl benzoate (MBPBA) is used as a modifier; When the waste plastic is a mixed plastic of polycarbonate (PC) and polybutylene terephthalate (PBT), 4-(3-acryloyloxy-2-ethoxy)phenylpropyl acetate (APPPA) is used as a modifier. Material formula: waste plastic is used as the base material, and modifiers, flame retardants, reinforcing agents, and auxiliary agents are added. The weight of each component is: 60-75 parts of waste plastic, 6-15 parts of modifiers, 10-12 parts of flame retardants, 5-8 parts of reinforcing agents, and 2-7 parts of auxiliary agents. Among them, the flame retardant includes magnesium hydroxide-aluminum hydroxide-phosphate melamine salt compound flame retardant, magnesium hydroxide-aluminum hydroxide compound flame retardant, melamine cyanurate (MCA), magnesium hydroxide (MH), red phosphorus (RP), etc.; reinforcing agents include glass fiber, carbon fiber, aramid fiber, composite reinforcement materials of waste carbon fiber and boron nitride nanotubes, etc.; auxiliary agents include antioxidant 1010, ultraviolet absorber UV-531, anti-ultraviolet agent UV-327, composite powder of nano zirconium dioxide and cerium oxide, etc. Material preparation process: After the waste plastic is crushed, it is premixed with other formula components in a high-speed mixer at a speed of 800-1200rpm for 15-20 minutes, and then enters a twin-screw extruder for melt blending at 160-270℃, with a screw speed of 150-170rpm. Then, according to different needs, corresponding products such as exterior wall material samples are made by injection molding, extrusion molding or compression molding. In some processes, such as the treatment of polybutylene terephthalate (PBT), the polyetheramine-grafted ethylene-vinyl acetate copolymer (EVA-g-PEPA) undergoes a cross-linking reaction through a dynamic vulcanization process during the blending process, and the molded material is pretreated with a UV aging box for weather resistance.

7. The method for recycling waste plastics according to claim 1, characterized in that: The synthesis method of 3-(4-(3-methacryloyloxypropoxy)-3-fluorophenyl)-5-(2-quinolyl)-1,2,4-triazole-5-thione (MFPQT) is as follows: 3-(4-(3-methacryloyloxypropoxy)-3-fluorobenzoic acid) and 2-quinolinecarboxylic acid hydrazide-5-thione are used as raw materials, 3-(4-(3-methacryloyloxypropoxy)-3-fluorobenzoic acid) is mixed with dicyclohexylcarbodiimide (DCC) and 4-dimethylaminopyridine (DMAP) in anhydrous dichloromethane, and the mixture is stirred at room temperature for 30 minutes to activate the carboxyl group, and then 2-quinolinecarboxylic acid hydrazide-5-thione is added, and the reaction is continued to be stirred at room temperature for 12 hours. After the reaction is completed, the precipitate is removed by filtration, the solvent is removed by distillation under reduced pressure, and the target product MFPQT is obtained by recrystallization with n-hexane and ethyl acetate; The synthesis method of 4-(2-(4-succinyloxybutoxy)-3-bromophenyl)-3-(5-methyl-2-pyrimidinyl)-1,2,4-oxadiazole-5-sulfide (SBPOT) is as follows: 4-(2-(4-succinyloxybutoxy)-3-bromobenzoic acid) and 5-methyl-2-pyrimidinecarboxylic acid hydrazide-5-sulfide are used as raw materials, 4-(2-(4-succinyloxybutoxy)-3-bromobenzoic acid) is reacted with dichlorothionyl in anhydrous toluene, and the reaction is refluxed at 65° C. for 2 hours to obtain the corresponding acid chloride, and then the acid chloride is added dropwise to an anhydrous ethanol solution containing 5-methyl-2-pyrimidinecarboxylic acid hydrazide-5-sulfide and triethylamine, and the reaction is stirred at room temperature for 10 hours. After the reaction is completed, the solvent is removed by distillation under reduced pressure, and the target product SBPOT is obtained by recrystallization with ethyl acetate and petroleum ether; The synthesis method of 5-(3-(3-itaconyliminoethoxy)-4-iodophenyl)-2-(5-fluoro-3-pyrazolyl)-1,3,4-thiadiazole-5-thione (IIPFT) is as follows: 5-(3-(3-itaconyliminoethoxy)-4-iodobenzoic acid) and 5-fluoro-3-pyrazolecarboxylic acid hydrazide-5-thione are used as raw materials, 5-(3-(3-itaconyliminoethoxy)-4-iodobenzoic acid) is mixed with N,N-dicyclohexylcarbodiimide (DCC) and 4-dimethylaminopyridine (DMAP) in anhydrous dichloromethane, and the mixture is stirred at room temperature for 30 minutes to activate the carboxyl group, and then 5-fluoro-3-pyrazolecarboxylic acid hydrazide-5-thione is added, and the reaction is continued to be stirred at room temperature for 12 hours. After the reaction is completed, the precipitate is removed by filtration, the solvent is removed by distillation under reduced pressure, and the mixture is recrystallized with n-hexane and ethyl acetate to obtain the target product IIPFT; The synthesis method of methyl 2-(acryloyloxy)benzoate (ABM) is as follows: methyl 2-hydroxybenzoate and acryloyl chloride are used as raw materials, in the presence of triethylamine, the molar ratio of triethylamine to methyl 2-hydroxybenzoate is 1.2-1.5:1, in anhydrous dichloromethane, the mass volume ratio of methyl 2-hydroxybenzoate to anhydrous dichloromethane is 1:5-1:8 (g / mL), acryloyl chloride is slowly added dropwise in an ice water bath at 0-10°C, the molar ratio of acryloyl chloride to methyl 2-hydroxybenzoate is 1.1-1.3:1, after the addition is completed, the reaction is stirred at room temperature for 3-4 hours, and then a separation and purification step is performed to obtain the ABM; The synthesis method of ethyl 3-(vinyloxy)benzoate (VOBAE) is as follows: ethyl 3-hydroxybenzoate and vinyl chloride are used as raw materials, under alkaline conditions, the molar ratio of alkali (such as sodium hydroxide) to ethyl 3-hydroxybenzoate is 1.5-2:1, in ethanol, the mass volume ratio of ethyl 3-hydroxybenzoate to ethanol is 1:6-1:10 (g / mL), reflux reaction is carried out at 60-70° C. for 4-6 hours, and then separation and purification steps are performed to obtain VOBAE; The synthesis method of 4-(methacryloyloxy)propyl benzoate (MAPBP) is as follows: 4-hydroxypropyl benzoate and methacryloyl chloride are used as raw materials, in the presence of triethylamine, the molar ratio of triethylamine to 4-hydroxypropyl benzoate is 1.3-1.6:1, in anhydrous toluene, the mass volume ratio of 4-hydroxypropyl benzoate to anhydrous toluene is 1:4-1:7 (g / mL), methacryloyl chloride is slowly added dropwise in an ice water bath at 0-10°C, the molar ratio of methacryloyl chloride to 4-hydroxypropyl benzoate is 1.2-1.4:1, after the addition is completed, the reaction is stirred at room temperature for 3-4 hours, and then a separation and purification step is performed to obtain; The synthesis method of 3-(acryloyloxy-2-methoxy) butyl benzoate (APMBB) comprises: using 3-hydroxy butyl benzoate and acryloyl chloride as raw materials, in the presence of triethylamine, the molar ratio of triethylamine to 3-hydroxy butyl benzoate is 1.2-1.5:1, firstly synthesizing 3-(acryloyloxy) butyl benzoate, the molar ratio of acryloyl chloride to 3-hydroxy butyl benzoate is 1.1-1.3:1, the reaction temperature is 0-10°C, and the reaction time is 3-4 hours; then reacting with 2-methoxy-3-chloropropane under alkaline conditions, the molar ratio of base (such as potassium hydroxide) to 3-(acryloyloxy) butyl benzoate is 1.3-1.7:1, reflux reaction is carried out at 60-70°C for 4-6 hours, and then performing separation and purification steps to obtain the product; The synthesis method of 4-(vinyl-3-acryloyloxy) isobutyl benzoate (VAPBIB) comprises: using 4-hydroxy isobutyl benzoate and vinyl-3-chloropropylene as raw materials, under alkaline conditions, the molar ratio of alkali (such as sodium carbonate) to 4-hydroxy isobutyl benzoate is 1.4-1.8:1, firstly synthesizing 4-(vinyl-3-hydroxy) isobutyl benzoate, the reaction temperature is 50-60°C, and the reaction time is 4-6 hours; then reacting with acryloyl chloride in the presence of triethylamine, the molar ratio of triethylamine to 4-(vinyl-3-hydroxy) isobutyl benzoate is 1.3-1.6:1, slowly dropping acryloyl chloride in an ice water bath at 0-10°C, the molar ratio of acryloyl chloride to 4-(vinyl-3-hydroxy) isobutyl benzoate is 1.2-1.4:1, stirring at room temperature for reaction for 3-4 hours after the dropwise addition is completed, and then performing a separation and purification step to obtain VAPBIB; The synthesis method of 3-(2-methyl-3-acryloyloxypropoxy)benzoic acid (MAPBA) is as follows: 3-(2-methyl-3-hydroxypropoxy)benzoic acid and acryloyl chloride are used as raw materials, in the presence of triethylamine, the molar ratio of triethylamine to 3-(2-methyl-3-hydroxypropoxy)benzoic acid is 1.2-1.5:1, in anhydrous dichloromethane, the mass volume ratio of 3-(2-methyl-3-hydroxypropoxy)benzoic acid to anhydrous dichloromethane is 1:5-1:8 (g / mL), acryloyl chloride is slowly added dropwise in an ice water bath at 0-10°C, the molar ratio of acryloyl chloride to 3-(2-methyl-3-hydroxypropoxy)benzoic acid is 1.1-1.3:1, after the addition is completed, the reaction is stirred at room temperature for 3-4 hours, and then a separation and purification step is performed to obtain MAPBA; The synthesis method of 4-(3-butenoyloxy-2-methoxypropoxy)phenylacetic acid (BMOPA) is as follows: 4-(3-hydroxy-2-methoxypropoxy)phenylacetic acid and crotonoyl chloride are used as raw materials; in the presence of triethylamine, the molar ratio of triethylamine to 4-(3-hydroxy-2-methoxypropoxy)phenylacetic acid is 1.3-1.6:1; in anhydrous toluene, the mass volume ratio of 4-(3-hydroxy-2-methoxypropoxy)phenylacetic acid to anhydrous toluene is 1:4-1:7 (g / mL); crotonoyl chloride is slowly added dropwise in an ice water bath at 0-10° C., the molar ratio of crotonoyl chloride to 4-(3-hydroxy-2-methoxypropoxy)phenylacetic acid is 1.2-1.4:1; after the addition is completed, the mixture is stirred at room temperature for reaction for 3-4 hours, and then a separation and purification step is performed to obtain BMOPA; The synthesis method of 3-(2-vinyl-3-acryloyloxy) methyl benzoate (VAPMB) is as follows: 3-(2-vinyl-3-hydroxy) methyl benzoate and acryloyl chloride are used as raw materials, in the presence of triethylamine, the molar ratio of triethylamine to 3-(2-vinyl-3-hydroxy) methyl benzoate is 1.2-1.5:1, in anhydrous dichloromethane, the mass volume ratio of 3-(2-vinyl-3-hydroxy) methyl benzoate to anhydrous dichloromethane is 1:5-1:8 (g / mL), acryloyl chloride is slowly added dropwise in an ice water bath at 0-10°C, the molar ratio of acryloyl chloride to 3-(2-vinyl-3-hydroxy) methyl benzoate is 1.1-1.3:1, after the addition is completed, the reaction is stirred at room temperature for 3-4 hours, and then a separation and purification step is performed to obtain VAPMB; The synthesis method of 3-(2-methyl-3-butenoyloxy)propyl benzoate (MBPBA) is as follows: 3-(2-methyl-3-hydroxy)propyl benzoate and crotonyl chloride are used as raw materials, in the presence of triethylamine, the molar ratio of triethylamine to 3-(2-methyl-3-hydroxy)propyl benzoate is 1.3-1.6:1, in anhydrous toluene, the mass volume ratio of 3-(2-methyl-3-hydroxy)propyl benzoate to anhydrous toluene is 1:4-1:7 (g / mL), crotonyl chloride is slowly added dropwise in an ice water bath at 0-10°C, the molar ratio of crotonyl chloride to 3-(2-methyl-3-hydroxy)propyl benzoate is 1.2-1.4:1, after the addition is completed, the reaction is stirred at room temperature for 3-4 hours, and then a separation and purification step is performed to obtain the product.

Citation Information

Cited By

  • High-strength regenerated PET composite material and preparation method thereof

    CN120059421A

  • Flexible cable material for robot and preparation method thereof

    CN120118509A

  • Anti-ultraviolet aramid fiber and preparation method thereof

    CN120330910A

  • A kind of anti-ultraviolet aramid fiber and preparation method thereof

    CN120330910B